Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1038/sj.bjp.0702877
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C co‐expression and the effects of halothane on rat skeletal muscle sodium channels

Abstract: 1 Voltage-gated Na channels, which are potential targets for general anaesthetics, are substrates for PKC, which phosphorylates a conserved site in the channel inactivation gate. We investigated the idea that PKC modulates the eect of volatile anaesthetics on Na channels via phosphorylation of this inactivation gate site. 2 Na currents through rat skeletal muscle Na channel a-subunits expressed in Xenopus oocytes were measured by two-microelectrode voltage clamp in the presence of the volatile anaesthetic agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Thus, sodium channels pass this test of anesthetic relevance. Studies of volatile anesthetic action on cloned sodium channels show somewhat divergent results that, in part, may be due to differences in the origin (neural versus nonneural origin of the channel) (148,158,159).…”
Section: -Htmentioning
confidence: 97%
“…Thus, sodium channels pass this test of anesthetic relevance. Studies of volatile anesthetic action on cloned sodium channels show somewhat divergent results that, in part, may be due to differences in the origin (neural versus nonneural origin of the channel) (148,158,159).…”
Section: -Htmentioning
confidence: 97%
“…Human Na v 1.4 heterologously expressed in Xenopus oocytes is inhibited by isoflurane and halothane,10 whereas rat Na v 1.4 in the same expression system was reported to be insensitive to halothane unless co-expressed with protein kinase C (PKC) 24. Our results indicate that rat Na v 1.4 expressed in a mammalian cell line is inhibited by multiple inhaled anesthetics in the absence of over-expression or pharmacological activation of PKC indicating that PKC activation is apparently not required for inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…This inactivation gate phosphorylation site is significant in the response of Na channels to halothane. We have previously shown that the enhancement of Na current decay induced by halothane in oocytes co‐expressing Na channels and PKC was absent in a Na channel mutant lacking this phosphorylation site ( Mounsey et al ., 1999 ). In the experiments reported here the mechanism of this effect was found to be a decrease in the amplitude of the slow phase of Na current decay, which resulted in a reduction of charge movement, and hence suppression of Na current.…”
Section: Discussionmentioning
confidence: 99%
“…Our methods for isolation and mRNA injection of Xenopus laevis oocytes have been described ( Mounsey et al ., 1995 ; 1999 ). Oocytes were defolliculated manually the day of the electrophysiologic experiments, 2–5 days after injection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation